A psycho-educational HIV/STI prevention intervention for internally displaced women in Leogane, Haiti: results from a non-randomized cohort pilot study. - Carmen H Logie (Public Library of Science (PLoS), 2014)
Background Little evidence exists regarding efficacious HIV and sexually transmitted infections (STI) prevention interventions with internally displaced populations. Internally displaced women are at elevated risk for HIV/STI due to limited access to health services, heightened poverty and social network breakdown. The FASY (Famn an Aksyon Pou Sante' Yo) (Women Taking Action For Their Health) study examined the effectiveness of a peer health worker (PHW) delivered psycho-educational HIV/STI pilot study with internally displaced women in Leogane, Haiti. Method This was a non-randomized cohort pilot study. Participants completed a computer-assisted pre-test programmed on Android tablet PCs followed by an HIV/STI educational video-based session and a 6-week psycho-educational group program of weekly meetings. Participants completed a post-test upon completion of group sessions. The primary outcome was HIV knowledge; our pre-specified index of clinically significant change was an effect size of 0.30. Secondary outcomes included: STI knowledge, condom use, social support, resilient coping, depression and relationship control. We used mixed-effects regression to calculate mean outcome pre-post score change. This study was registered (clinicaltrials.gov, NCT01492829). Results Between January 1-April 30, 2012 we assigned 200 participants to the study. The majority of participants (n = 176, 88%) completed the study and were followed up at 8 weeks, finishing April 30, 2012. Adjusted for socio-demographic characteristics, HIV knowledge (β = 4.81; 95% CI 4.36-5.26), STI knowledge (β = 0.84; 95% CI 0.70-0.99), condom use (AOR = 4.05, 95% CI 1.86-8.83), and depression (β = -0.63, 95% CI -0.88--0.39) scores showed statistically significant change post-intervention (p<0.05). Conclusions This pilot study evaluated a PHW psycho-educational HIV/STI prevention intervention among internally displaced women in post-earthquake Haiti. Pilot studies are an important approach to understand feasibility and scientific impacts of HIV prevention strategies in disaster contexts. Study results may inform HIV prevention interventions among internally displaced women in Haiti and can be tested for applicability with internally displaced women globally. ClinicalTrials.gov: Identifier NCT01492829, URL: http://clinicaltrials.gov/ct2/show/NCT01492829?term=logie&rank=1.